Kerahiman: Sikap Pastoral Paus Fransiskus Melawan Budaya Kebencian - Sudhiarsa, Raymundus I Made (Perspektif, 2017)
The article tries to paraphrase the apostolic message of Pope Francis on the occasion of the World Mission Sunday 2016 entitled “Missionary Church, Witness of Mercy” by highlighting some key points which are particularly important for fostering and keepingalive the missionary impulse of the Church. As sanctorum communio, the Church is by all means also called to ‘go out’ to the world, to share the joy of the Gospel and God’s tenderness and compassion,particularly where injustices, wars, and humanitarian crises prevail. The Pontiff reminds that this hard work needsa lot of patience and effort with maternal services or with that of the merciful vine-dresser of the Gospel. In so-doing the missionary Church is witnessing God’s mercy